Risk Management in Parallel Projects: Analysis & Best Practices and Implications to Generic DBrain (gDBrain) Research Project - Ibrahim, Jamaludin; Wani, Sharyar; Elsadig Adam, Mutasim; Abdullahi, Husein Osman; Shamsudin, Ahmad Faizul (2013)
The increased stiffness in competition has dramatically increased the risk occurrence in project delivery. As the number of projects grows, enterprises or project managers have to eventually run simultaneous projects. Risk management in such cases becomes extremely necessary as failure of one project may lead to the near failure of all the parallel projects running under the same supervision. Therefore, it becomes necessary to understand the best practices for risk management in a parallel project operation environment. Though the issue is of high importance, yet not much has been discussed. This study was carried out in an enterprise environment whereby professionals of this field with high experience were interviewed and requested to share their experiences. The research results bear witness to the fact that risk is inevitable and leaves a strong negative impact on all the projects operating in parallel. As such there is a high need to understand the strategies and best practices that are being applied in this field to avoid heavy losses. We seek to apply lessons learned to managing the DBrain research project which has multiple collaborators working in parallel.